Randomized Trial of Communication Facilitators to Reduce Family Distress and Intensity of End-of-Life Care - Curtis, J. Randall; Treece, Patsy D.; Nielsen, Elizabeth L.; Gold, Julia; Ciechanowski, Paul S.; Shannon, Sarah E.; Khandelwal, Nita; Young, Jessica P.; Engelberg, Ruth A. (American journal of respiratory and critical care medicine, 2016)
Communication with family of critically ill patients is often poor and associated with family distress. To determine if an intensive care unit (ICU) communication facilitator reduces family distress and intensity of end-of-life care. We conducted a randomized trial at two hospitals. Eligible patients had a predicted mortality greater than or equal to 30% and a surrogate decision maker. Facilitators supported communication between clinicians and families, adapted communication to family needs, and mediated conflict. Outcomes included depression, anxiety, and post-traumatic stress disorder (PTSD) among family 3 and 6 months after ICU and resource use. We identified 488 eligible patients and randomized 168. Of 352 eligible family members, 268 participated (76%). Family follow-up at 3 and 6 months ranged from 42 to 47%. The intervention was associated with decreased depressive symptoms at 6 months (P = 0.017), but there were no significant differences in psychological symptoms at 3 months or anxiety or PTSD at 6 months. The intervention was not associated with ICU mortality (25% control vs. 21% intervention; P = 0.615) but decreased ICU costs among all patients (per patient: $75,850 control, $51,060 intervention; P = 0.042) and particularly among decedents ($98,220 control, $22,690 intervention; P = 0.028). Among decedents, the intervention reduced ICU and hospital length of stay (28.5 vs. 7.7 d and 31.8 vs. 8.0 d, respectively; P < 0.001). Communication facilitators may be associated with decreased family depressive symptoms at 6 months, but we found no significant difference at 3 months or in anxiety or PTSD. The intervention reduced costs and length of stay, especially among decedents. This is the first study to find a reduction in intensity of end-of-life care with similar or improved family distress. Clinical trial registered with www.clinicaltrials.gov (NCT 00720200).